WOMEN REPRESENTATION AND STOCK LIQUIDITY - Zaitul, Zaitul; Sandra, Viola Refina; Ilona, Desi; Yunilma, Yunilma; Hamdi, Mukhlizul (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2023)
ABSTRACTThis study investigates the effect of women's representation in supervisory boards and stock market liquidity. Hence, this paper also determines the impact of women's representation in supervisory boards independent and women with a business education background in the supervisory board on stock market liquidity. Thus, four control variables are involved here: company size, company age, company leverage, and company profitability. Twenty-two publicly listed companies operated in Restaurant, hotel, and tourism sub-sector from the 2017-2018 period are used as research samples. The multivariate regression analysis is applied, and the secondary data is gathered from mutli-sources are analyzed using SPSS and Gretl. The finding shows a positive effect of women's representation in supervisory boards and stock market liquidity. In addition, women's representation in the supervisory board independent is positively related to stock market liquidity. Finally, the relationship between the women with business education backgrounds on the supervisory board and stock market liquidity is negatively documented. Hence, stock market liquidity is also positively related to firm size. Practical and theoretical inferences are discussed in the paper.Keywords: Women representation in the supervisory board, women representation in supervisory board independent, women with a business education background in the supervisory board, stock market liquidity